Revolutionizing learning in the digital age: a systematic literature review of microlearning strategies - Alias, Nurul Fitriah; Razak, Rafiza Abdul (Interactive learning environments, 2025)
In today's rapidly evolving digital landscape, the quest to enhance learning experiences and outcomes has never been more pressing. This systematic literature review delves into the world of microlearning strategies to examine their role in addressing the challenges of learning in the digital age. Microlearning, characterized by its bite-sized, easily digestible content, is gaining prominence as a powerful tool for learners and organizations seeking effective, just-in-time knowledge acquisition. This review systematically examines the current body of research, focusing on microlearning strategies and their impact on enhancing learning outcomes. It explores the diverse array of microlearning techniques, from bite-sized content delivery and mobile learning to video-based learning and social learning, dissecting their effectiveness in different contexts. It also investigates the challenges educational institutions may face during the implementation of microlearning initiatives and proposes strategies to overcome these hurdles. Through an in-depth exploration of scholarly sources, this systematic review provides insights into the benefits of microlearning, its future trends, and recommendations for organizations aiming to leverage microlearning strategies to enhance learning outcomes. As digital technologies continue to reshape the educational landscape, this review serves as a comprehensive resource for educators, trainers, and decision-makers navigating the dynamic terrain of modern education.